The effectiveness of reference librarians - Belem, Moctar; Wan Mamat, Wan Ali; Abu Bakar, Ahmad Bakeri (IIUM Press, 2011)
The librarians deal with information explosion in various ways. The reference librarians face many challenges relating to information explosion. In order to cope with these challenges, they rely heavily upon training. The strategy they use to deal with information explosion is to focus on quality of information rather than quantity, this in reference to the way they exchange information. They also use a variety of technology and digital resources to cope with information explosion, with heavy emphasis on the internet, digital books and various library automation software programs.